Multi pH-sensitive polymer–drug conjugate mixed micelles for efficient co-delivery of doxorubicin and curcumin to synergistically suppress tumor metastasis. (19th August 2020) - Zhou, Yuanhang; Zhou, Chuhang; Zou, Yang; Jin, Yao; Han, Shidi; Liu, Qi; Hu, Xinping; Wang, Leqi; Ma, Yining; Liu, Yan
Abstract : Multi pH-responsive polymer-drug conjugate mixed micelles were fabricated to co-deliver doxorubicin and curcumin for synergistic suppression tumor metastasis via inhibiting the invasion, migration, intravasation and extravasation of tumor cells. Abstract : Combination therapy has been proved to be an effective strategy to inhibit metastasis, however, its efficacy is always compromised by the poor delivery efficiency of drugs. In this study, multi pH-sensitive polymer–drug conjugate mixed micelles were fabricated by the self-assembly of PEOz-PLA-ace-Cur, a conjugate of curcumin (Cur) with poly(2-ethyl-2-oxazoline)-poly(d, l -lactide) (PEOz-PLA) through the linkage of the pH-cleavable acetal bond, and PEOz-PLA-imi-DOX, a conjugate of doxorubicin (DOX) with PEOz-PLA through the linkage of the pH-cleavable benzoic imine bond. The mixed conjugate micelles (PP-Cur/PP-DOX-Mix-PMs) with accurately and conveniently controlled mass ratio of the two drugs were demonstrated to have a small particle size (40–128 nm), high drug loading capacity and pH-dependent drug release behavior. Notably, PP-Cur5/PP-DOX1-Mix-PMs exhibited slower DOX release under physiological conditions compared with PEOz-PLA-imi-DOX micelles, resulting in deeply reduced side effects in vivo . Furthermore, the mixed conjugate micelles showed synergistically enhanced inhibition of MDA-MB-231 cell growth and metastasis evidenced by the results of in vitro anti-invasion, wound healing and anti-migration assessment, and in vivo bioluminescence imaging in nude mice, and significant reduction of the side effects of DOX compared with dual drug physically loaded polymeric micelles. Mechanistic studies demonstrated that the possible inhibitory mechanism of PP-Cur5/PP-DOX1-Mix-PMs on tumor metastasis could be assigned to their inhibition of the invasion, migration, intravasation and extravasation of tumor cells. In conclusion, the multi pH-sensitive polymer–drug conjugate mixed micelles with synergistically enhanced anti-tumor and anti-metastasis activity are potential candidates for safe and effective cancer combination therapy.